Analisis Wacana Struktural dalam Pidato Politik Donald Trump 21 Juni 2025: Address To The American People - Bustam, Muhammad Rayhan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study aims to examine the discourse structure of U.S. President Donald Trump’s speech on June 21, 2025, using a structural discourse analysis approach. The approach investigates the text through three main levels: macrostructure, microstructure, and superstructure along with interpretative analysis focusing on tone, emotion, and persuasive strategies. The data were obtained from the official transcript of Trump’s “Address to the American People” published by the Miller Center. The study applies a descriptive qualitative method grounded in van Dijk’s, Halliday and Hasan’s, and Barthes’ frameworks. Findings reveal that the speech demonstrates coherence between global meaning (macrostructure) and its linguistic and organizational structures. Interpretatively, the speech exhibits a persuasive tone, patriotic emotion, and rhetorical strategies that combine ethos, pathos, and logos to construct political and moral legitimacy. This study affirms that structural discourse analysis can effectively uncover meaning dynamics and power relations in modern political communication. Keywords: Structural Discourse Analysis, Political Speech, Donald Trump, Rhetoric